(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Oxidative stress induces imbalance between prooxidant and antioxidant level, which results in production of reactive oxygen species (ROS). The ROS in excess react with macromolecules of the cell- fatty acid, DNA, protein, and thus, cause damage the macromolecules surpassing the natural antioxidant defense mechanisms and thus, contributing several chronic diseases. Reserpine (0.38mg/kg body weight) was injected intraperitoneally in Wistar Albino rats to develop depression. The stressed rats were treated with orange fleshed sweet potato (OFSP) and carrot, and the nutraceutical- vitamin C. Depression alleviation was evaluated by analysis of plasma stress marker malondialdehyde (MDA), superoxide dismutase (SOD) and nitrous oxide (NO). The functional food and nutraceutical reduce oxidative stress indicated by biochemical stress markers- MDA level decline and SOD and NO rise significantly. Hence, the functional food and nutraceutical having antioxidant potential- phenols and carotenoids, may be effective in alleviation of stress induced depression.